2018
DOI: 10.1002/jmri.26578
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent diffusion MRI to distinguish malignant from benign head and neck tumors

Abstract: Background There is growing interest in the effect of diffusion time on apparent diffusion coefficient (ADC) values in cancers; however, little evidence exists regarding its utility to differentiate malignant from benign head and neck tumors. Purpose To investigate the utility of ADC value changes in distinguishing between malignant and benign head and neck tumors using the different diffusion times obtained from oscillating gradient spin‐echo (OGSE) and pulsed gradient spin‐echo (PGSE) MRI sequences. Study Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 31 publications
3
33
2
Order By: Relevance
“…The observed decrease in ADC and sADC values with T d in breast tumors was in agreement with the literature, as were the results of our previous investigation 11,32,42 . This con rms the hypothesis that diffusion hindrance in tumors increases when the T d value increases, as more molecules might hit the increased number of obstacles such as cell membranes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observed decrease in ADC and sADC values with T d in breast tumors was in agreement with the literature, as were the results of our previous investigation 11,32,42 . This con rms the hypothesis that diffusion hindrance in tumors increases when the T d value increases, as more molecules might hit the increased number of obstacles such as cell membranes.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported that various types of malignant tumors revealed the decrease in ADC values with long T d [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…in tumor applications. 25,26,28 Here we demonstrated the technical feasibility and clinical utility of t d -dependent dMRI in neonatal HIE, which is a potentially favorable application as the high ADC and T2 relaxation time in the neonatal brain mitigated the technical issues of OG-dMRI. We were able to reliably detect t d -dependence from PG-and OG-dMRI measurements in the neonatal brain tissues, and we found higher DADC in the subcortical WM compared to deep GM.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the performance of OG-dMRI is limited by the relatively low gradient strength on clinical systems, which leads to the limited oscillating frequency range, low b-value, and low signal-to-noise ratio (SNR). Nevertheless, OG-dMRI has been attempted in tumor, [25][26][27][28] stroke patients, 29,30 and healthy adult brain 31,32 given these technical limitations. Particularly, Baron et al 29 performed OG and PG-dMRI scans in 11 stroke patients and the results suggested that the ADC differences between OG and PG scans, which represented the t d -dependence, increased in the lesion areas.…”
Section: Introductionmentioning
confidence: 99%
“…That does not disregard that technical innovation of new sequences or the improvement of quantitative accuracy; however, it underlines that the accuracy is only a piece of the big picture. Reproducibility, scalability, adaptability, and generalizability are also essential when faced with clinical implementation.…”
mentioning
confidence: 99%